Comparison of television broadcasting standards by analytic hierarchy process - Безрук, Валерий Михайлович; Скорик, Юлия Валериевна (Eastern-European Journal of Enterprise Technologies, 2013)
Today, there are different standards for television broadcasting, each of them is characterized by a set of controversial technical and economic indicators. For choosing a preferable standard and its implementation in broadcast television networks, it is necessary to use methods of multi-criteria selection of optimal designs. The paper analyzes and compares two standards of digital TV broadcasting: DVB-T standard with multi-frequency modulation COFDM and ATSC standard with 8-level single-frequency amplitude modulation with vestigial sideband SSB-8T. The standards are compared using the Saaty method taking into account a set of quality indicators. Some quantitative results are given, characterizing the practical aspects of applying the method of Saaty for choosing the preferable variant of television broadcasting. The analytic hierarchy process was considered, which allows formalized selection of the optimal design with a set of quality parameters based on subjective judgments of experts. As a result of the expert survey, the matrixes of paired comparisons of quality parameters and speech codecs were formulated. After processing of expert judgments the corresponding eigenvectors and vectors of priorities for different levels of the modulation comparison hierarchy were estimated. These estimations were used for calculating the parameters of priorities global vector components. According to the analytic hierarchy process based on the maximum value of the priorities global vector components the preferable standard of television broadcasting DVB-T with a multi-frequency modulation SOFDM was chosen.